Primary school teachers' perceptions of teacher competencies realization levels - Gokyer, Necmi (Sila Science, 2012)
The aim of this study is to determine primary school teachers' perceptions of teacher competency realization levels. The universe of the study carried out using survey model consists of 2993 teachers who work at 49 primary schools in central district of Elazig province during 2009-2010 education-teaching year. It constitutes 800 form and branch teachers working at 26 schools determined through using simple random sampling method. For the research, a questionnaire was prepared for performance indicators in the study named Ministry of National Education (MEB) General Competencies for Teaching Profession and applied resorting to expert opinions. The sample of the research constitutes 404 teachers. Teachers see themselves competent at always level at program and content knowledge, school, family and community relations, teaching and learning process and knowing student dimensions and at usually level at personal and professional values-professional development and learning, monitoring and evaluation of development dimensions.
Keywords: General competencies for teaching; Primary school: Form and branch teacher; Teaching profession; Perception of teaching competence